2005
DOI: 10.1088/0031-9155/50/3/001
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation and evaluation of the γ index and the γ index angle for the verification of IMRT hybrid plans

Abstract: In IMRT, the method for a quantitative comparison of two-dimensional dose distributions is still under development. The gamma evaluation method proposed by Low et al is the most accepted approach and has been adapted by many groups. Based on the concept of Low et al we developed a software tool with an intelligent search algorithm to minimize the calculation time. For the interpretation of deviations a y angle distribution and other tools (dose difference map, profiles, y area histograms, etc) are integrated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 23 publications
1
95
0
4
Order By: Relevance
“…The example shows the regions that fail the criteria ͑3% and 3 mm in this case͒, highlighting areas of significant failure. Stock et al 164 also identified the fact that the angle that the ␥ vector makes to the spatial axes ͑the complement to the angle the vector makes to the dose axis͒ can be used to determine whether the ␥ discrepancy is due to a spatial or dose error. An example of the ␥ angle is shown in Fig.…”
Section: Ivb4a Composite Toolmentioning
confidence: 99%
See 2 more Smart Citations
“…The example shows the regions that fail the criteria ͑3% and 3 mm in this case͒, highlighting areas of significant failure. Stock et al 164 also identified the fact that the angle that the ␥ vector makes to the spatial axes ͑the complement to the angle the vector makes to the dose axis͒ can be used to determine whether the ␥ discrepancy is due to a spatial or dose error. An example of the ␥ angle is shown in Fig.…”
Section: Ivb4a Composite Toolmentioning
confidence: 99%
“…6͑b͒. 164 While the ␥ angle may be useful in evaluating the failure reasons, it is very sensitive to dose distribution noise and can be difficult to visually evaluate.…”
Section: Ivb4a Composite Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…We recommend performing a gamma evaluation with a criterion of at least 3%/3mm (96,102), if possible using absolute dosimetry. For a 2D and 3D evaluation all measured points with a dose below 10% of the reference dose should be discarded to avoid false positives due to low signal-to-noise in the low dose area.…”
Section: Gamma Analysismentioning
confidence: 99%
“…For the effectiveness and success of the treatment prescribed,a high spatial and dosimetric accuracy during treatment delivery is of crucialimportance.Therefore, particular quality assurance (QA) procedureshave been developed together with those increasingly sophisticatedtreatment techniques [1]- [3], which wouldinclude the verification of absolute doses at one or more reference points as well as of twodimensionaldose distributions in different planes in awater-equivalent phantom.…”
Section: Introductionmentioning
confidence: 99%